2011
DOI: 10.1017/s0212610911000188
|View full text |Cite
|
Sign up to set email alerts
|

Transport costs and economic growth in a backward economy: the case of Peru, 1820-1920

Abstract: This paper analyses the system of transportation and discusses the effect of geography and transport infrastructure on transport costs and economic growth in Peru during the 19 th and early 20 th centuries. Using primary and secondary sources, I find that geography imposed difficult transport challenges on Peruvians during this period. There were no navigable rivers in coastal and highland regions, railroads were scarce and most roads were inadequate for wagons, sometimes even for horses and mules. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Finally, Deustua (2009) analyzes the impact of railroads on the mining sector in the central highlands. Recently, Zegarra (2011) shows that railroads were less costly than the traditional system of mules and llamas, which had an important impact on the growth of copper, sugar and cotton sectors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, Deustua (2009) analyzes the impact of railroads on the mining sector in the central highlands. Recently, Zegarra (2011) shows that railroads were less costly than the traditional system of mules and llamas, which had an important impact on the growth of copper, sugar and cotton sectors.…”
Section: Introductionmentioning
confidence: 99%
“…III, p. 10). 9 Zegarra (2011). markets, but even in this country, as wheat, coffee, cacao, and so on prove, which for the coastal consumer now come largely from abroad -even when interior growers can supply them in sufficient quantity, even superior quality" 10 . Later in 1860, Manuel Pardo indicated that the construction of railroads would reduce transportation costs dramatically, allowing the exploitation of natural resources, especially in the central highlands 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On pre‐railway transport infrastructure in Spanish America, see Gutiérrez Álvarez, Las comunicaciones ; see also Summerhill, Order against progress , for Brazil; Clark, ‘Railway building’, for Ecuador; Coatsworth, Growth against development , for México; and Zegarra, ‘Transport costs and economic growth’ for Peru. In some cases, such as Mexico, the transport system experienced an involution between the end of the colonial period and the 1870s, with a decrease in wheeled traffic and an increase in the use of pack animals; see Riguzzi, ‘Los caminos del atraso’.…”
mentioning
confidence: 99%